SOCIO-ANTHROPOLOGICAL ANALYSIS OF ‘ASHABIYYAH HADITHS - Fauji, Hayatul; Arifin, Tajul; Sadikin, Moch. Ramdan Hasan (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
This article dissects the ‘ashabiyyah (fanaticism) hadith. Analysis of the ‘ashabiyyah hadith aims to understand the messages and values contained therein and their implementation in modern society. The ‘ashabiyyah hadiths chosen as the basis for this research are those which explicitly mention the word ‘ashabiyyah, along with their derivations. The ‘ashabiyyah hadith is analyzed using the syarh approach used by hadith experts and then reviewed using a socio-anthropological science approach. The theory used is Anthony Giddens’ social constitution which is supported by anthropological facts about the Arab people revealed in the Sirah Nabawiyah books and Ibn Khaldun’s theory of ‘ashabiyyah. From the results, it was found that the Prophet was a social agent who changed the tribalistic order of life of the Arab nation into a civil society, without eliminating it as a whole. He still maintained the positive values of jahiliyyah, but changed his motives or intentions. This was seen when he discussed with his friends regarding ‘ashabiyyah which has become the DNA of Arab people anthropologically. The concept of `ashabiyyah, whose basis can be religion, kinship, clanism, tribalism, ethnicity, ideology, economic and political interests, regionalism, and so on, is not only a characteristic of tribal (Arab) societies of the past, but also of modern societies and countries of post-colonial nations, including Indonesia. [Artikel ini membedah hadis ‘ashabiyyah (fanatisme). Analisa hadis ‘ashabiyyah bertujuan memahami pesan dan nilai yang terkandung di dalamnya serta implementasinya terhadap masyarakat modern. Hadis-hadis ‘ashabiyyah yang dipilih sebagai basis penelitian ini ialah yang secara eksplisit menyebut kata ‘ashabiyyah, berikut derivasinya. Hadis ‘ashabiyyah dianalisa menggunakan pendekatan syarh yang digunakan oleh ahli hadis kemudian ditinjau ulang menggunakan pendekatan ilmu sosio-antropologi. Teori yang digunakan ialah konstitusi sosial Anthony Giddens yang didukung dengan fakta antropologis bangsa Arab yang diungkapkan dalam kitab-kitab sirah nabawiyah dan teori Ibn Khaldun tentang ‘ashabiyyah. Dari hasil penelitian ditemukan bahwa Nabi adalah agen sosial yang mengubah tatanan kehidupan bangsa Arab yang bersifat kesukuan menjadi masyarakat madani, tanpa menghilangkannya secara menyeluruh. Beliau tetap mempertahankan nilai-nilai positif jahiliyah, tetapi mengubah motif atau niatnya. Hal itu terlihat ketika beliau berdiskusi dengan para sahabat berkenaan dengan ‘ashabiyyah yang secara antropologis telah menjadi DNA masyarakat Arab. Konsep ‘ashabiyyah yang basisnya dapat berupa agama, kekerabatan, klanisme, kesukuan, etnisitas, ideologi, kepentingan ekonomi dan politik, kedaerahan, dan sebagainya, tidak saja menjadi ciri masyarakat kesukuan (Arab) masa lalu, tetapi juga masyarakat modern dan negara-negara bangsa pascakolonial, termasuk Indonesia.]